Tobacco impact on quality of life, a cross-sectional study of smokers, snuff-users and non-users of tobacco - Solbrith Wachsmann; Lena Nordeman; Annika Billhult; Gun Rembeck (BMC, 2023)
Abstract Background Tobacco smoking is a major public health issue, and also affects health-related quality of life. There has been considerable debate as to whether oral moist snuff, a form of tobacco placed in the oral cavity between the upper lip and gum as in sublabial administration, can be considered a safe alternative to smoking. The aim of this study was to investigate the association between health-related quality of life and smoking, snuff use, gender and age. Method This cross-sectional study included 674 women and 605 men aged 18 to 65 recruited through a Swedish population database. Subjects completed a questionnaire about tobacco use and the 36-item Short Form Health Survey (SF-36). Multivariable logistic regression analyses were performed for the association between health-related quality of life and tobacco use, gender and age. The median perceived health-related quality of life (SF-36) for an age-matched Swedish population was used as the cutoff: above the cutoff indicated better-than-average health coded as 1, or otherwise coded as 0. The independent variables were smoking (pack-decades), snuff-use (box-decades), gender and age in decades. The outcome was presented as the Odds Ratio (OR) with a 95% confidence interval (CI) for each independent variable. Results The experience of cigarette smoking is associated with decreased physical functioning (PF), general health (GH), vitality (VT), social functioning (SF) and mental health (MH) as well as both lower physical component summary (PCS) and mental component summary (MCS). Further, the experience of snuff use is associated with bodily pain (BP), lower VT, and lower PCS. In the study population older age is associated with lower PF,GH, VT, MH, PCS and MCS. Female gender is associated with lower PF and VT. Conclusion This study shows that smoking is associated with lower health-related quality of life. The results also illuminate the detrimental health effects of using snuff, implying that snuff too is a health hazard. As studies on the bodily effects of snuff are relatively scarce, it is imperative that we continue to address and investigate the impact on the population using snuff on a regular basis. Trial registration ClinicalTrials.gov ID NCT05409963 05251022 08/06/22.